Small and overlooked: Roman glass counters from archaeological sites in Poland. (February 2023) - Krzyżanowska, Marta; Syta, Olga; Kępa, Luiza; Wagner, Barbara
Highlights: The analysis of imported Roman glass sheds new light on the context of glass exchange. The first archeometric study of Roman glass counters form the territory of Poland. Glass composition was determined by LA-ICP-MS. Chronological distinction is visible in the base glass used to make white glass. Abstract: From the 1st century onwards, the flow of the imported glass objects into the territory of Barbaricum rises. A selection of 47 glass counters from archaeological sites in Poland dated to Roman Iron Age were gathered and analysed by LA-ICP-MS. The paper provides the data on the composition of different glass colours. These glasses were of the soda-lime-silica type, and were mostly made using Roman natron glass. Colourants and opacifiers were added to the glass – for most counter colours this was Sb-Mn recycled glass. For the white glass counters however, there is a chronological distinction in the type of base glass used. The first group, dated to phase B1-B2 (ca. the second half of the 1st century–160 CE), used Mn-decolourised glass, while the second group, dated from phase B2/C1-C1a (160/180–230 CE) and later, was probably produced with Sb-decolourised glass. One of the conclusions proposes further research into imported white glass found at Polish archaeological sites.